2020
DOI: 10.1530/rep-20-0054
|View full text |Cite
|
Sign up to set email alerts
|

Birth of offspring from spermatid or somatic cell by co-injection of PLCζ-cRNA

Abstract: Artificial oocyte activation is important for assisted reproductive technologies, such as fertilization with round spermatids (ROSI) or the production of cloned offspring by somatic cell nuclear transfer (SCNT). Recently, phospholipase Cζ (PLCζ)-cRNA was used to mimic the natural process of fertilization, but this method required the serial injection of PLCζ-cRNA and was found to cause damage to the manipulated oocytes. Here we tried to generate offspring derived from oocytes that were fertilized using round s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…It is known that the success rate of offspring production decreases signi cantly when FD spermatozoa are used compared to the use of intact spermatozoa (average birth rate from fresh spermatozoa were around 60%, whereas from FD spermatozoa were around 20%) 6,34 . It is also known that the success rate of offspring production decreases largely when fresh spermatids are used compared to when fresh spermatozoa are used (average birth rate from fresh spermatozoa were around 60%, whereas from fresh round spermatid were around 20%) 12,13 . Thus, the synergistic negative effect of both methods (FD treatment and the use of spermatids) would have greatly reduced the success rate of FD spermatids.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is known that the success rate of offspring production decreases signi cantly when FD spermatozoa are used compared to the use of intact spermatozoa (average birth rate from fresh spermatozoa were around 60%, whereas from FD spermatozoa were around 20%) 6,34 . It is also known that the success rate of offspring production decreases largely when fresh spermatids are used compared to when fresh spermatozoa are used (average birth rate from fresh spermatozoa were around 60%, whereas from fresh round spermatid were around 20%) 12,13 . Thus, the synergistic negative effect of both methods (FD treatment and the use of spermatids) would have greatly reduced the success rate of FD spermatids.…”
Section: Discussionmentioning
confidence: 99%
“…To collect spermatids, the seminiferous tubules of the testes were minced using sharp scissors, as described previously 13 ; the only difference was that the cells were suspended in HEPES-buffered CZB medium 12 . In order to collect spermatozoa, we rst collected epididymides and cut their ducts using sharp scissors, as described previously 28 .…”
Section: Preparation Of Fd Spermatids and Fd Spermatozoamentioning
confidence: 99%
See 1 more Smart Citation
“…It was demonstrated that human spermatozoa devoid of PLCζ1 failed to induce Ca 2+ release and were unable to initiate the first step of embryo development (Yoon et al, 2008), while injection of recombinant human PLCζ1 induced intracellular calcium oscillations and oocyte activation in mouse and human oocytes (Swann et al, 2012;Yoon et al, 2012;Yamaguchi et al, 2017). Therefore, PLCζ has been used to induce Ca 2+ oscillations for assisted oocyte activation or artificial oocyte activation (AOA) (Amdani et al, 2013;Anifandis et al, 2019;Hirose et al, 2020). Barberan et al (2022) reviewed the advantages and disadvantages of using PLCζ1 as a diagnostic marker or therapeutic molecule in human ICSI procedures.…”
Section: Calcium Oscillationsmentioning
confidence: 99%
“…In particular, genetic defects in oocytes or early embryos can be compensated by introducing exogenous protein or synthetic mRNA (sometimes called complementary RNA, cRNA). For example, defects in egg activation due to mutations in the sperm-borne protein phospholipase C ζ1 (PLCZ1) can be rescued by recombinant protein or cRNA [91][92][93]. Proof-of-principle for the oocyte cRNA correction approach has also been reported for mutations in WEE2,…”
Section: Treatment Of Genetically Caused Infertilitymentioning
confidence: 99%